Independent surgical validation of the new prostate cancer grade‐grouping system. (19th April 2016) - Spratt, Daniel E.; Cole, Adam I.; Palapattu, Ganesh S.; Weizer, Alon Z.; Jackson, William C.; Montgomery, Jeffrey S.; Dess, Robert T.; Zhao, Shuang G.; Lee, Jae Y.; Wu, Angela; Kunju, Lakshmi P.; Talmich, Emily; et al.
Abstract : Objective: To report the independent prognostic impact of the new prostate cancer grade‐grouping system in a large external validation cohort of patients treated with radical prostatectomy (RP). Patients and methods: Between 1994 and 2013, 3 694 consecutive men were treated with RP at a single institution. To investigate the performance of and validate the grade‐grouping system, biochemical recurrence‐free survival (bRFS) rates were assessed using Kaplan–Meier tests, Cox‐regression modelling, and discriminatory comparison analyses. Separate analyses were performed based on biopsy and RP grade. Results: The median follow‐up was 52.7 months. The 5‐year actuarial bRFS for biopsy grade groups 1–5 were 94.2%, 89.2%, 73.1%, 63.1%, and 54.7%, respectively ( P < 0.001). Similarly, the 5‐year actuarial bRFS based on RP grade groups was 96.1%, 93.0%, 74.0%, 64.4%, and 49.9% for grade groups 1–5, respectively ( P < 0.001). The adjusted hazard ratios for bRFS relative to biopsy grade group 1 were 1.98, 4.20, 5.57, and 9.32 for groups 2, 3, 4, and 5, respectively ( P < 0.001), and for RP grade groups were 2.09, 5.27, 5.86, and 10.42 ( P < 0.001). The five‐grade‐group system had a higher prognostic discrimination compared with the commonly used three‐tier system (Gleason score 6 vs 7 vs 8–10). Conclusions: In an independent surgical cohort, we have validated the prognostic benefit of the new prostate cancer grade‐grouping system for bRFS, and shown that the benefit is maintained after adjusting for important clinicopathological variables. The greater predictive accuracy of the new system will improve risk stratification in the clinical setting and aid in patient counselling.